Transformation of Nahdlatul Ulama (NU) Islamic Education: From a Religious-Conservative Approach to a Religious-Rational-Sociological Concept in the Modern Era - Mujahid, Mujahid (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This research aims to explore and formulate an ideal educational model for Nahdlatul Ulama (NU) in the modern era by investigating the transition of NU Islamic education from a religious-conservative approach to a religious-rational-sociological one while maintaining core Islamic values. Design/methods/approach – Employing a historical method, this study involves a systematic analysis of historical data, documents, archives, and relevant literature to understand the evolution of NU Islamic education and its interaction with social and cultural changes. Findings – The research finds that NU Islamic education has transformed from a traditional religious-conservative approach to a more inclusive model, incorporating religious-rational and sociological aspects. This change encompasses revisions in teaching methodology, curriculum, and the educational orientation of Islamic boarding schools (pondok pesantren), emphasizing integrating religious education with rational and social aspects. Research implications – These findings significantly contribute to the discourse on the modernization of Islamic education, recommending the importance of holistic adaptation and innovation to meet the current generation's needs. The implications of this study are relevant for policymakers and educational practitioners in Indonesia and globally, demonstrating how Islamic education can evolve while maintaining its relevance in the modern era.